PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2022-2023) - Pratama, Mohammad Rian; Utami, Endang Sri (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The worth of a firm is a crucial element. This is because it can reflect how well a corporation performs. Company performance consists of various components, one of which is financial performance. Investors often use financial performance as a parameter when making stock investment decisions. This study aimed to prove whether financial performance affects the value of companies in the property and real estate sector listed on the Indonesia Stock Exchange from 2022-2023. The population observed in this study is all companies in the property and real estate sector listed on the Indonesia stock exchange for 2022-2023. The sample collection uses certain criteria better known as purposive sampling, so there are 60 sample companies, and the total research data is 120. The analysis method is done by applying the classical assumption test and multiple linear analysis, with a decision stating that the data is normally distributed and free from all symptoms of basic assumptions in regression analysis. Hypothesis testing reveals that partial results of liquidity, profitability, and activity variables can affect firm value, while solvency variables cannot affect firm value. For simultaneous testing, liquidity, solvency, profitability, and activity variables can affect firm value. The outcomes of this study are expected to participate in the development of financial theory which will certainly help enrich the understanding of how firm financial elements influence value and can accommodate financial analysts in making more informed decisions.